(untitled) (Global Journal of Management and Business Research, 2014)
The Export processing zone (EPZ) has been playing a vital role in Bangladesh economy after 1990 although for the first time it was established in the year 1983. In Bangladesh, it has contributed very effectively in the economy in terms of the foreign direct investment (FDI), export and employment for the last ten years especially in Bangladesh’s Export-Processing Zones (BEPZs). This study intends to explore the EPZ’s performance and its benefits in Bangladesh economy in terms of employment, investment and volume of export in details. It attempts to examine eight BEPZs performance in terms of their size, location, and infrastructure and find out why foreign investors are interested to get involved in BEPZs. This study focuses on the performance of the BEPZs between 1983 and 2012. Data (authentic secondary source) were being collected from the Bangladesh Export Processing Zone (BEPZA) official website.